Formation of Polysubstituted Pyridin-2-one Derivatives by Michael Addition of 3-Oxobutanamide to ?,?-Ethylenic Ketones and Amides - DRAPER, SYLVIA MARY; MC MURRY, THOMAS (My University, 1997)
Reaction of 3-oxobutanamide with 4-phenylbut-3-en-2-one and with 3-aryl-2-cyanoprop-2-enamides and related compounds affords new di-, tetra- and hexa-hydropyridin-2-one derivatives, the degree of unsaturation of the product depending on the experimental conditions.
PUBLISHED
Keywords: Chemistry